The winter food and feeding habits of Shelduck in the Camargue, France - Walmsley, John G; Moser, Michael E (Wildfowl, 1981)
The wintering Shelduck Tadorna tadorna population of the Mediterranean coast of France numbers 1,500-2,000 individuals. These inhabit a series of non-tidal hyper-saline lagoons, quite unlike those of northern Europe. The diet of Shelduck in the salines of the Camargue was restricted by the very low diversity of available food items. The study was based on faecal analysis and direct observations in the field. The most important food types were algal bioderm, Artemia and aquatic Coleoptera adults. Unique feeding methods characterized each food type. Each food type only became available under specific meteorological conditions (rain-fall, wind and evaporation). The availability of the most important food (algal bioderm) was determined by rainfall, which maintained the substrate moist for feeding. The numbers of Shelduck using the study area over two different winters 1977-78 and 1978-79 is correlated with the precipitation.